Aktuelles zum gesetzlichen Früherkennungsprogramm des Zervixkarzinoms in Deutschland - Behrens, Annika; Beckmann, Matthias; Stübs, Frederik (gynäkologische praxis, 2023)
The statutory cancer screening program (GKFP) covers regulations for early detection and screening of cancer for men and women in Germany. Costs for these assessments are covered by the health insurance. The G-BA is in charge of the organized screening, in which women between 20 and 34 years of age are entitled to a yearly screening assessment based on cytology smears. Women of 35 years and older are offered a combination of HPV testing and cytology every 3 years. Data showed a reduced incidence of invasive carcinoma of the cervix as well as of precancerous lesions and overall mortality. Participation in screening assessments for cervical cancer is recommended independently of HPV vaccination status for all women in the according age range. Prophylactic vaccination against HPV high risk types are recommended for all children and adolescents independently of the gender between 9–14 years of age, but before the first sexual intercourse. However, the license according to the European Medicines Agency (EMA) covers all children irrespective of the gender starting at 9 years of age without defining an upper age limit. At the moment, two HPV vaccines are available. For both vaccines, a 2-dose-vaccination regimen is recommended. HPV vaccination can also be valuable for adolescents and adults older than 17 years and to reduce reinfection rates after HPV infection. In this case, HPV vaccination is solely a prophylactic measure and has no therapeutic effect.
CRIS-Team Scopus Importer:2023-10-20
Keywords: cervical carcinoma; primary prevention; prophylactic vaccination; screening

Breast volume assessment with a smart phone device compared to MRI - Behrens, Annika; Wunderle, Marius; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Emons, Julius; Heindl, Felix; Hack, Caroline; Ohlmeyer, Sabine; Uder, Michael; Beckmann, Matthias; Fasching, Peter (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Comparative assessment of breast volume using a smartphone device versus MRI - Behrens, Annika; Hübner, Hanna; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Heindl, Felix; Emons, Julius; Hack, Carolin; Nabieva, Naiba; Uder, Michael; Wetzl, Matthias; Wunderle, Marius; et al. (Breast Cancer, 2024)
Background: Assessment of breast volume has a relevance for aesthetic surgery and for the prevention and prediction of breast diseases. This study investigated breast volume measurements using a three-dimensional (3D) body surface scanner integrated in a smartphone device in comparison with magnetic resonance imaging (MRI) scans. Methods: Breast volume was assessed for 22 women who underwent routine MRI imaging. 3D surface images were acquired using a smartphone’s digital texture camera (iPhone 11 Pro Max, Apple, California, USA, 2019). Breast volumes were manually outlined and calculated by two independent investigators using a 3D software tool (Meshmixer 3.5, Autodesk, Inc., 2018). Volume assessments from MRI images were performed by a radiologist using Syngo.via (Siemens Healthcare, Erlangen, Germany, VB50). The agreement between both methods and the inter-observer agreement was calculated with the concordance correlation coefficients and analysed with Bland–Altman plots. Results: The mean breast volume as determined by MRI volumetry was 771.0 ml on the left side and 763.9 ml on the right side. Utilizing the 3D body surface volume assessment method, the mean breast volume was measured as 660.3 ml (observer A) and 616.8 ml (observer B) on the left side, and 701.9 ml (observer A) and 638.6 ml (observer B) on the right side. Although a high correlation was observed, differences in volume measurements appeared more pronounced in cases of larger breast volume. Conclusions: Smartphone-based 3D assessment of breast volume sufficiently agreed with MRI-based breast volume. This new technique could be used for cosmetic breast assessments in a surgical context and possibly in breast cancer risk studies assessing breast volume as outcome parameters.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Breast volume; MRI; Smartphone; Three-dimensional (3D)

Concordance Rate of Colposcopy in Detecting Cervical Intraepithelial Lesions - Stübs, Frederik; Dietl, Anna; Behrens, Annika; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul; Koch, Martin C. (Diagnostics, 2022)
Background: The purpose of this research is to estimate the rate of concordance, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of colposcopy for high-grade squamous lesions and carcinomas (HSIL+). Methods: We conducted a retrospective study of colposcopies performed in the certified Dysplasia Unit in Erlangen between January 2015 and May 2022 (7.5 years). The colposcopic findings were correlated with biopsies obtained during examinations or surgery. Cases without histology were excluded. The primary outcome was the rate of concordance between the colposcopic and histological findings in relation to the type of transformation zone (TZ), examiner's level of experience and age of the patients. Results: A total of 4778 colposcopies in 4001 women were analyzed. The rates of concordance for CIN I/LSIL, CIN II/HSIL, CIN III/HSIL, and carcinoma were 43.4%, 59.5%, 78.5%, and 53.9%, respectively. The rate of concordance was lowest for TZ3 and highest for colposcopists with more than 10 years' experience. Conclusions: Colposcopy is an important, feasible, and effective method. Careful work-up needs to be performed for women with TZ3 who are over 35 years old, as they are at the highest risk of being misdiagnosed. The highest concordance for detecting HSIL+ was seen for colposcopists with >10 years' experience.
CRIS-Team WoS Importer:2022-11-11

Correction to: Comparative assessment of breast volume using a smartphone device versus MRI (Breast Cancer, (2025), 32, 1, (166-176), 10.1007/s12282-024-01647-6) - Behrens, Annika; Hübner, Hanna; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Heindl, Felix; Emons, Julius; Hack, Carolin; Nabieva, Naiba; Uder, Michael; Wetzl, Matthias; Wunderle, Marius; et al. (Breast Cancer, 2025)
The article ‘Comparative assessment of breast volume using a smartphone device versus MRI’, written by Annika S. Behrens, Hanna Huebner, Lothar Häberle, Marc Stamminger, Daniel Zint, Felix Heindl, Julius Emons, Carolin C. Hack, Naiba Nabieva, Michael Uder, Matthias Wetzl, Marius Wunderle, Matthias W. Beckmann, Peter A. Fasching, Sabine Ohlmeyer, was originally published under exclusive license to The Author(s), under exclusive licence to The Japanese Breast Cancer Society. As a result of the subsequent decision to publish the article under the open access model, the article’s copyright notice was changed on 12 February 2025 to © The Author(s) 2025 and the article is now distributed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The original article has been corrected.
CRIS-Team Scopus Importer:2025-03-21

Correction to: Evaluation of endocervical curettage (ECC) in colposcopy for detecting cervical intraepithelial lesions (Archives of Gynecology and Obstetrics, (2024), 310, 6, (3037-3045), 10.1007/s00404-024-07721-w) - Behrens, Annika; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Koch, Martin C.; Schulmeyer, Carla; Seibold, Anja; Gaß, Paul; et al. (Archives of Gynecology and Obstetrics, 2025)
The article “Evaluation of endocervical curettage (ECC) in colposcopy for detecting cervical intraepithelial lesions”, written by “Annika S. Behrens · Anna K. Dietl · Werner Adler · Carol Geppert · Arndt Hartmann · Antje Knöll · Matthias W. Beckmann · Grit Mehlhorn · Martin C. Koch · Carla E. Schulmeyer · A. Seibold · Paul Gass · Frederik A. Stuebs” was originally published under exclusive license to “The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024”. As a result of the subsequent decision to publish the article under the open access model, the article’s copyright notice was changed on 12 February 2025 to © The Author(s) 2025 and the article is now distributed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0. Open access funding enabled and organized by Projekt DEAL.
CRIS-Team Scopus Importer:2025-05-02

Correlation of RANK and RANKL with mammographic density in primary breast cancer patients - Wunderle, Marius; Heindl, Felix; Behrens, Annika; Häberle, Lothar; Hack, Carolin; Heusinger, Katharina; Hübner, Hanna; Gaß, Paul; Rübner, Matthias; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; et al. (Archives of Gynecology and Obstetrics, 2024)
Purpose: The receptor activator of nuclear factor kappa B (RANK) and its ligand (RANKL) have been shown to promote proliferation of the breast and breast carcinogenesis. The objective of this analysis was to investigate whether tumor-specific RANK and RANKL expression in patients with primary breast cancer is associated with high percentage mammographic density (PMD), which is a known breast cancer risk factor. Methods: Immunohistochemical staining of RANK and RANKL was performed in tissue microarrays (TMAs) from primary breast cancer samples of the Bavarian Breast Cancer Cases and Controls (BBCC) study. For RANK and RANKL expression, histochemical scores (H scores) with a cut-off value of > 0 vs 0 were established. PMD was measured in the contralateral, non-diseased breast. Linear regression models with PMD as outcome were calculated using common predictors of PMD (age at breast cancer diagnosis, body mass index (BMI) and parity) and RANK and RANKL H scores. Additionally, Spearman rank correlations (ρ) between PMD and RANK and RANKL H score were performed. Results: In the final cohort of 412 patients, breast cancer-specific RANK and RANKL expression was not associated with PMD (P = 0.68). There was no correlation between PMD and RANK H score (Spearman’s ρ = 0.01, P = 0.87) or RANKL H score (Spearman’s ρ = 0.04, P = 0.41). RANK expression was highest in triple-negative tumors, followed by HER2-positive, luminal B-like and luminal A-like tumors, while no subtype-specific expression of RANKL was found. Conclusion: Results do not provide evidence for an association of RANK and RANKL expression in primary breast cancer with PMD.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Breast cancer; Immunohistochemistry; Mammographic density; RANK expression; RANKL expression

Cytology and HPV Co-Testing for Detection of Vaginal Intraepithelial Neoplasia: A Retrospective Study. - Stübs, Frederik; Dietl, Anna; Koch, Martin C.; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Mehlhorn, Grit; Beckmann, Matthias; Schulmeyer, Carla; Heindl, Felix; Emons, Julius; et al. (Cancers, 2023)
(1) Background: Vaginal intraepithelial neoplasia (VaIN) is a rare premalignant disease caused by persistent human papillomavirus (HPV) infection. Diagnosing VaIN is challenging; abnormal cytology and positive HPV tests are usually the first signs, but published data on their accuracy for detecting it are rare and contradictory. The aim of this study is to compare the results of hrHPV and cytology co-testing with the histological findings of the vagina. (2) Methods: In the certified Dysplasia Unit at Erlangen University Hospital, cytology and HPV samples from the uterine cervix or vaginal wall after hysterectomy were obtained between 2015 and 2023 and correlated with histological findings in biopsies from the vaginal wall. Women without vaginal biopsy findings or concomitant cervical disease were excluded. (3) Results: In all, 279 colposcopies in 209 women were included. The histological results were: benign (n = 86), VaIN I/vLSIL (n = 116), VaIN II/vHSIL (n = 41), VaIN III/vHSIL (n = 33), and carcinoma (n = 3). Accuracy for detecting VaIN was higher in women with previous hysterectomies. Positive HPV testing during colposcopy increased the likelihood for VaIN II/III/vHSIL threefold. The detection rate for VaIN III/vHSIL was 50% after hysterectomy and 36.4% without hysterectomy. (4) Conclusions: Women with risk factors for VaIN, including HPV-16 infection or prior HPV-related disease, need careful work-up of the entire vaginal wall. Hysterectomy for HPV-related disease and a history of cervical intraepithelial neoplasia (CIN) also increased the risk for VaIN II/III/vHSIL.
EVALuna2:540622

Evaluation of a Wireless Localization System for Nonpalpable Breast Lesions - Feasibility and Cost-effectiveness in Everyday Clinical Routine - Heindl, Felix; Schulz-Wendtland, Rüdiger; Jud, Sebastian; Erber, Ramona; Hack, Carolin; Preuss, Caroline; Behrens, Annika; Pöschke, Patrik; Emons, Julius (In Vivo, 2022)
BACKGROUND/AIM: Smaller, earlier-stage breast tumors are being found in breast cancer screening, and neoadjuvant chemotherapy is the gold standard when chemotherapy is indicated. Precise marking and localization of the tumor are thus becoming increasingly important. Wire-free localization techniques are under investigation in order to reduce presurgical radiography, pain, the risk of wire dislocation, and allow scheduling flexibility for patients and surgery departments. PATIENTS AND METHODS: This single-center observational study from June 2020 to October 2021 included 15 patients with mammographically or sonographically detected nonpalpable breast lesions. Radiofrequency identification (RFID) tags were placed preoperatively under ultrasound or radiologic guidance to localize lesions for planned surgery. All patients underwent breast conservation surgery, including one bilateral and one targeted axillary dissection. RESULTS: Histology identified two benign and 13 malignant lesions, including three ductal carcinomas in situ and 11 invasive breast cancers. Placement, control radiography, and handling of the RFID tag were feasible in everyday routine for different radiologists and surgeons and managed cost-effectively. All of the RFID tags were found in the specimen radiographs. CONCLUSION: The feasibility and cost-effectiveness of this non-wire localization method were demonstrated in this rather small cohort of patients. Further studies including larger numbers of patients are needed to confirm the method's accuracy.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Breast cancer; localization; RFID; surgery

Evaluation of endocervical curettage (ECC) in colposcopy for detecting cervical intraepithelial lesions - Behrens, Annika; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Koch, Martin C.; Schulmeyer, Carla; Seibold, Anja; Gaß, Paul; et al. (Archives of Gynecology and Obstetrics, 2024)
Purpose: Diagnostic challenges in colposcopy arise especially in women aged 50 or older, with postmenopausal status and transformation zone type 3 (TZ3). Endocervical curettage (ECC) is a valuable tool for diagnosing intracervical lesions. The aim of this retrospective analysis was to evaluate the use of ECC in colposcopy for detecting cervical intraepithelial lesions. Methods: A retrospective study was carried out of colposcopies performed in the certified Dysplasia Unit at Erlangen University Hospital between July 2016 and June 2023. Pap and human papillomavirus (HPV) results were correlated with the histologic findings via ECC, obtained during examinations or surgery. The primary outcome was the rate of accuracy between the colposcopic and histologic findings with regard to cytology, age of patients, and type of transformation zone (TZ). Results: A total of 429 colposcopies in 413 women with histologic samples obtained via ECC were included in the final analysis. In all, 355 women had TZ3. Among patients with TZ3, evidence of high-grade lesions and invasive carcinoma was also found in women with normal or low-grade abnormal cytology. For patients with normal colposcopic findings, cervical intraepithelial neoplasia (CIN) 2 and CIN 3/adenocarcinoma in situ (AIS) were found in 56 patients (16%), and invasive carcinoma was found in four patients (0.1%). Conclusion: This analysis suggests that ECC is a valuable tool in the diagnosis of cervical intraepithelial neoplasia, especially for patients who present with a normal colposcopy of the cervix and vagina but have either recurrent abnormal cytologic findings or high-grade abnormal cytology indicating CIN 2 +.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Cervical cancer; Cervical cancer screening assessment; Cervical intraepithelial neoplasia; Colposcopy; Cytology; Endocervical curettage

Genome-wide and transcriptome-wide association studies of mammographic density phenotypes reveal novel loci - Chen, Hongjie; Fan, Shaoqi; Stone, Jennifer; Thompson, Deborah J.; Douglas, Julie; Li, Shuai; Scott, Christopher; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Li, Christopher; et al. (Breast Cancer Research, 2022)
BACKGROUND: Mammographic density (MD) phenotypes, including percent density (PMD), area of dense tissue (DA), and area of non-dense tissue (NDA), are associated with breast cancer risk. Twin studies suggest that MD phenotypes are highly heritable. However, only a small proportion of their variance is explained by identified genetic variants. METHODS: We conducted a genome-wide association study, as well as a transcriptome-wide association study (TWAS), of age- and BMI-adjusted DA, NDA, and PMD in up to 27,900 European-ancestry women from the MODE/BCAC consortia. RESULTS: We identified 28 genome-wide significant loci for MD phenotypes, including nine novel signals (5q11.2, 5q14.1, 5q31.1, 5q33.3, 5q35.1, 7p11.2, 8q24.13, 12p11.2, 16q12.2). Further, 45% of all known breast cancer SNPs were associated with at least one MD phenotype at p < 0.05. TWAS further identified two novel genes (SHOX2 and CRISPLD2) whose genetically predicted expression was significantly associated with MD phenotypes. CONCLUSIONS: Our findings provided novel insight into the genetic background of MD phenotypes, and further demonstrated their shared genetic basis with breast cancer.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Breast cancer; Genome-wide association study (GWAS); Mammographic density; Transcriptome-wide association study (TWAS)

Impact of the Corona Pandemic on Cervical Cancer Screening Assessment - Stübs, Frederik; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Koch, Martin C.; Mehlhorn, Grit; Beckmann, Matthias; Theuser, Anna Katharin; Schulmeyer, Carla; et al. (In Vivo, 2024)
BACKGROUND/AIM: The global impact of the COVID-19 pandemic resulted in disruptions to healthcare systems throughout the world. The numbers of cytology examinations, human papillomavirus (HPV) tests, and women referred for colposcopy decreased in many countries. There have been no reports on cervical cancer screening in Germany. This study aimed to describe changes in the numbers of colposcopies, cytology examinations, HPV tests, and histological results during the pandemic compared to the pre-pandemic years in order to evaluate the impact of the COVID-19 pandemic on cervical cancer screening. PATIENTS AND METHODS: The numbers of colposcopies, cytology examinations, HPV tests, and histologic results were analyzed retrospectively for the period January 2018 to December 2022. The 2 years period before the pandemic (2018 and 2019) were compared with the 3 years period of the pandemic (2020-2022). RESULTS: In total, 6,518 colposcopies were performed in 5,579 women. The numbers of colposcopies, cytology examinations, and high-risk HPV (hrHPV) tests increased during the pandemic years. The number of biopsies per year taken was stable (range=450-554). The relative numbers of cervical intraepithelial neoplasia (CIN) III/HSIL findings were stable, while the numbers of cervical cancers identified increased slightly from 15 (6.6%) in 2018 to 22 (7.4%) in 2022. CONCLUSION: Increases in numbers of women examined and colposcopies were observed in the years 2021 and 2022 during the pandemic, in comparison to the preceding years. These also led to increases in the figures for cytology, hrHPV, histology, and operations. The onset of the pandemic occurred in the same year as a newly organized screening program started in Germany. The increases might therefore be due to the newly organized screening system.
CRIS-Team Scopus Importer:2024-03-15
Keywords: cervical cancer; cervical cancer screening; cervical dysplasia; COVID-19 pandemic; High-grade squamous intraepithelial lesion (HSIL)

Kolposkopie der Vulva: Wann, wie, wie oft? - Behrens, Annika; Beckmann, Matthias; Gaß, Paul; Schulmeyer, Carla; Seibold, Anja; Dietl, Anna; Stübs, Frederik (gynäkologische praxis, 2025)
Various changes can occur in the vulvar region, which can be of inflammatory origin or caused by autoimmune diseases but can also represent precancerous lesions and invasive carcinomas. Many of these changes are accompanied by symptoms of itching or pain but can also be completely asymptomatic. On the basis of the G-BA diagnostic algorithm, there are no specific recommendations for the use of colposcopy in the evaluation of abnormal vulvar findings. A detailed history of symptoms and knowledge of the physiological anatomy are particularly important. An initial assessment is always performed as part of the cancer screening examination. In the context of further diagnostics, colposcopy of the vulva with targeted histological sampling is helpful. Depending on the diagnosis, various therapeutic procedures are available. The follow-up intervals of HSIL of the vulva are not uniformly regulated and should be adapted to the individual patient‘s risk and the existing disease. Especially in in patients with a history of vulvar HSIL, lifelong follow-up is indicated, whereas vulvar carcinoma is followed up regularly for 5 years.
CRIS-Team Scopus Importer:2025-01-31
Keywords: carcinoma; colposcopy; dysplasie; vulva; vulvar cancer

Management of Cervical Intraepithelial Neoplasia in Pregnant Women - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Schulmeyer, Carla; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; et al. (Anticancer Research, 2023)
BACKGROUND/AIM: The aims of the present study were to evaluate the accuracy of colposcopic findings, investigate the way in which untreated cervical intraepithelial neoplasia (CIN) 2/3 develops during pregnancy, and identify factors associated with regression, persistence, or progression rates. PATIENTS AND METHODS: In a tertiary gynecology and obstetrics department, 655 pregnant women were seen for colposcopy. The most common reason for referral was abnormal cytology findings. The follow-up findings were analyzed retrospectively on the basis of colposcopic findings and cytological and histological tests. RESULTS: The rate of accuracy for major colposcopic findings was 89.2%. Among the colposcopic findings considered "suspicious for invasion" were invasive carcinoma in 42.9% and CIN 3 in 57.1%. The persistence of CIN 3 postpartum was 80% and the rate of progression 4.1%. The rate of regression for CIN 3 was 21.9%. For CIN 2, the rate of persistence was 37.5%, with a regression rate of 31.3%. The rate of regression was higher after vaginal delivery in comparison with caesarean section. CONCLUSION: The accuracy rate of colposcopy is comparatively high, at 89.2%. This might be because pregnant women are seen by more experienced examiners in our dysplasia unit. The rate of progression is comparable with that in other studies. Vaginal delivery increases the regression rate. The newborns' birth weight or birth week did not affect the rates of regression or persistence.
CRIS-Team Scopus Importer:2023-07-07
Keywords: cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); mode of delivery; pregnancy; treatment

Personal Profiling im Bereich der Senologie - Behrens, Annika; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna; Emons, Julius (Die Radiologie, 2025)
Background: The concept of personalized medicine is becoming increasingly important. The possibilities of diagnostics include not only genetic and molecular tumor profiles, but also the use of precise and individual imaging techniques. Objectives: The development and implementation of suitable diagnostic procedures with high sensitivity and specificity, which are at the same time tailored to the individual risk factors and biological characteristics of the patient, remain a challenge. Materials and methods: To enable personalized profiling, comprehensive diagnostics must be established that take into account all parameters such as imaging, molecular and genetic markers as well as real-world data and the use of artificial intelligence. This article sheds light on different approaches to personalized diagnostics in breast cancer and highlights the current clinical standard, innovative areas of research and the resulting challenges. Conclusion: The highest hurdles for newer imaging techniques are the standardization of image analysis and the validation of these techniques in large clinical trials. The use of artificial intelligence requires not only appropriate technical and medical expertise, but also a sensitive approach to issues such as data protection and patient privacy. Real-world registries offer insights into real world treatment situations and are therefore of great importance.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Artificial intelligence; Big data—mammography; Breast cancer; Breast diagnostics; Early detection

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Prognostic Significance of the Detection of Human Papilloma Virus L1 Protein in Smears of Cervical Intraepithelial Neoplasia Grade 3 in Pregnant Women - Stübs, Frederik; Dietl, Anna; Schulmeyer, Carla; Behrens, Annika; Seibold, Anja; Brückner, Lena; Schleicher, Oliver; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Hartman, Arndt; Knöll, Antje; et al. (Anticancer Research, 2025)
Background/Aim: Cervical intraepithelial neoplasia (CIN) III/high-grade squamous lesions (HSIL) remains a significant challenge during pregnancy. Current data on the course of disease are contradictory, with cases of progression to cervical cancer (CC) during pregnancy being observed. Evidence suggests that the expression of L1 capsid protein is associated with a favorable prognosis in non-pregnant women.
CRIS-Team Scopus Importer:2025-02-14
Keywords: cervical cancer; CIN III/HSIL; Colposcopy; L1 capsid protein; pregnancy

RANK and RANKL Expression in Tumors of Patients with Early Breast Cancer - Behrens, Annika; Wurmthaler, Lena; Heindl, Felix; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hack, Carolin; Emons, Julius; Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Rübner, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction The receptor activator of nuclear factor-κB (RANK) pathway was associated with the pathogenesis of breast cancer. Several studies attempted to link the RANK/RANKL pathway to prognosis; however, with inconsistent outcomes. We aimed to further contribute to the knowledge about RANK/RANKL as prognostic factors in breast cancer. Within this study, protein expression of RANK and its ligand, RANKL, in the tumor tissue was analyzed in association with disease-free survival (DFS) and overall survival (OS) in a study cohort of patients with early breast cancer. Patients and Methods 607 samples of female primary and early breast cancer patients from the Bavarian Breast Cancer Cases and Controls Study were analyzed to correlate the RANK and RANKL expression with DFS and OS. Therefore, expression was quantified using immunohistochemical staining of a tissue microarray. H-scores were determined with the cut-off value of 8.5 for RANK and 0 for RANKL expression, respectively. Results RANK and RANKL immunohistochemistry were assessed by H-score. Both biomarkers did not correlate (ρ = -0.04). According to molecular subtypes, triple-negative tumors and HER2-positive tumors showed a higher number of RANK-positive tumors (H-score ≥ 8.5), however, no subtype-specific expression of RANKL could be detected. Higher RANKL expression tended to correlate with a better prognosis. However, RANK and RANKL expression could not be identified as statistically significant prognostic factors within the study cohort. Conclusions Tumor-specific RANK and RANKL expressions are not applicable as prognostic factors for DFS and OS, but might be associated with subtype-specific breast cancer progression.
CRIS-Team Scopus Importer:2023-12-22
Keywords: breast cancer; immunohistochemistry; prognosis; RANK; RANKL

Rare Case Report - Mucoepidermoid Carcinoma (MEC) of the Vulva - Dietl, Anna; Stübs, Frederik; Schulmeyer, Carla; Behrens, Annika; Hartmann, Arndt; Agaimy, Abbas; Beckmann, Matthias; Gaß, Paul (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Standardized Procedures for Patients with Dysplasia and Other Diseases of the Cervix, Vulva, and Vagina at a Certified Dysplasia Unit Prior to the Introduction of the Organized Cervical Cancer Screening Program. - Schulmeyer, Carla; Koch, Martin C.; Dietl, Anna; Stübs, Frederik; Behrens, Annika; Renner, Simone K.; Mehlhorn, Grit; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckmann, Matthias; Gaß, Paul (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Gynecologic dysplasia units and dysplasia consultations are obliged to offer diagnosis and treatment in accordance with the guidelines. The organization of the consultation process, management of patient appointments, diagnosis, and treatment algorithms are heterogeneous. The legislation arising from the new Federal Joint Committee decision, dated 22 November 2018, concerning the organized cervical cancer screening program has been in force since 1 January 2020. In this article we provide an overview of the existing structures and interdisciplinary cooperation of specialized dysplasia units incorporated in certified gynecologic cancer center. Materials and Methods We carried out a retrospective database search of data collected prospectively from 1 July 2014 to 31 December 2019 at the dysplasia unit at the Department of Gynecology and Obstetrics, Erlangen University Hospital, which was the first dysplasia unit to be certified in 2014. Results A total of 5594 patients presented at the unit, and 16061 colposcopic, vulvoscopic, and anoscopic examinations were performed. Approximately 4100 examinations of the cervix, vagina, vulva, and anus are carried out each year, 1600 of these were exclusively cervix colposcopies. A total of 12197 cytology results were assessed, as well as 4850 histology results, and 8193 high-risk HPV tests. The quality indicators required by the dysplasia unit for annual recertification were met each year. Conclusion Certified dysplasia units and consultations form the central component in the algorithm for further investigating abnormal screening results; but they are also the first point of contact for a large number of patients with acute or chronic complaints in the genital region.
EVALuna2:542837

Update Breast Cancer 2021 Part 1-Prevention and Early Stages - Stickeler, Elmar; Aktas, Bahriye; Behrens, Annika; Belleville, Erik; Ditsch, Nina; Fasching, Peter; Fehm, Tanja N.; Hartkopf, Andreas D.; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; et al. (Geburtshilfe und Frauenheilkunde, 2021)
This review summarises not only the latest evidence on prevention, but also the current research on the treatment of early-stage breast cancer patients. Recent years have seen a growing body of evidence on the risk of high- and moderate-penetrance breast cancer susceptibility genes. A large international consortium has now been able to further refine the answer to the question of the significance of the so-called panel genes. Moreover, the data on treatment selection regarding endocrine efficacy and the decision for or against chemotherapy have also been advanced markedly. There is also new data on adjuvant CDK4/6 (cyclin-dependent kinase 4/6) inhibitors, which are standard in first-line treatment in patients with metastatic HER2-negative, hormone receptor-positive (HR+) breast cancer. For other therapies such as immune checkpoint inhibitors, which have successfully improved the rate of pathologic complete response (pCR) in neoadjuvant treatment settings for patients with triple-negative breast cancer (TNBC), there is a growing understanding of the quality of life and side effects. This is especially important in situations where patients could possibly be cured without such a regimen.
CRIS-Team WoS Importer:2021-05-21

Update Breast Cancer 2021 Part 2-Advanced Stages, Long-Term Consequences and Biomarkers - Ditsch, Nina; Stickeler, Elmar; Behrens, Annika; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Hartkopf, Andreas D.; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lueftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2021)
This review summarises and discusses significant aspects of recently published studies on patient treatment in advanced breast cancer and on biomarkers in breast cancer. In recent years, a large number of drugs for all molecular subtypes have been developed up to phase III trials. With regard to immune checkpoint inhibitors in metastasised breast cancer, the recent discussion has centred on the best candidate for combined chemotherapy. The oral taxanes could become a new type of oral chemotherapies. There is a growing body of data on biomarkers for the use of CDK4/6 inhibitors, which could also signify further development for other molecular subtypes. New substances have been developed for metastatic HER2+ breast cancer that still result in good remission even after massive prior treatment and/or cerebral metastasis. Similarly, knowledge is growing about targeted therapies with antibody-drug conjugates (ADC) against Trop-2, which could bolster our therapeutic armoury in triple-negative breast cancer (TNBC). In addition, the clinical focus is on understanding how to maintain fertility after breast cancer treatment. Here, pooled analyses provide new insights.
CRIS-Team WoS Importer:2021-05-21

Update Breast Cancer 2021 Part 3 – Current Developments in the Treatment of Early Breast Cancer: Review and Assessment of Specialised Treatment Scenarios by an International Expert Panel - Fehm, Tanja N.; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans Christian; Lüftner, Diana; Müller, Volkmar; Schütz, Florian; Thomssen, Christoph; Belleville, Erik; Behrens, Annika; et al. (Geburtshilfe und Frauenheilkunde, 2021)
The continuous availability of findings from new studies repeatedly results in updated treatment recommendations and guidelines. In the case of breast carcinoma in particular, several studies have been published in the last few years that have transformed how early and advanced breast carcinoma is being treated. However, this by no means means implies that there is agreement among all experts on specific issues. It is precisely the diversity of interpretation of guidelines and study findings that reflects the constantly changing available data and its complexity, as well as the availability of new drugs. In recent years, new substances such as pertuzumab, T-DM1, neratinib and capecitabine have become available to treat patients with early stages of breast carcinoma. Furthermore, the first results on the use of CDK4/6 inhibitors for adjuvant treatment have now been published. Last but not least, the use of multigene tests to avoid the necessity of chemotherapy in certain patients is still under discussion. This review summarises the state of the data and publishes the results of the survey completed by experts at the 2021 St. Gallen Breast Cancer Conference on early-stage breast cancer.
CRIS-Team Scopus Importer:2021-07-02
Keywords: early breast cancer; expert panel; therapy decisions

Uterus didelphys and cervical cancer: A case report - Krückel, Annika; Saatze, Miriam; Behrens, Annika; Beckmann, Matthias; Pöschke, Patrik; Emons, Julius (Gynecologic Oncology Reports, 2024)
Background: Deficiencies in the merging process of the paramesonephric ducts as part of the embryonal development lead to anomalies of the uterus, cervix, fallopian tubes and proximal vagina (Müllerian malformations). The co-occurrence with cervical cancer is rare and there are no standardized protocols for managing urogenital anomalies in the realm of oncologic treatment for gynecological carcinomas. Case report: A symptom-free 41-year-old woman (gravida 0) presented at our clinic with an externally obtained AGC-FN (atypical glandular cells – favor neoplastic) finding in the Papanicolaou (Pap) smear test and persistent positivity for human papillomavirus (HPV) type 16. Sample biopsies from the portio vaginalis uteri confirmed a cervical intraepithelial neoplasia (CIN) III/ high grade squamous intraepithelial lesion (HSIL), invasive carcinoma could not be ruled out. The examinations revealed the incidental finding of a uterus didelphys and renal agenesis on the left side. After cervical conization, the patient was diagnosed with squamous cell carcinoma of the cervix. Guideline-compliant treatment with laparotomic hysterectomy according to Piver type II following a staging laparoscopy with sentinel lymphadenectomy was performed. A customized protocol was used for the indocyanine green (ICG) injection as part of the sentinel lymph node examination, tailored to the patient's anatomical characteristics. Discussion: Müllerian malformations may impede detection and treatment of gynecological carcinomas. Individualized therapy planning is necessary to meet the anatomical peculiarities of the genital anomaly. In instances of concomitant urinary tract anomalies, protective measures are imperative to safeguard normal kidney function. Conclusion: The current case demonstrates the successful implementation of guideline-compliant therapy for early-stage cervical cancer in an individual with Müllerian malformation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Cervical cancer; Urogenital anomaly; Uterus didelphys

Vitamin B-Can it prevent cognitive decline? A systematic review and meta-analysis - Behrens, Annika; Grässel, Elmar; Pendergrass, Anna; Donath, Carolin (Systematic Reviews, 2020)
BACKGROUND: Development of cognitive decline represents substantial issues in today's society, steadily gaining importance with increasing life expectancy. One potential approach to preventing cognitive decline is to lower homocysteine by administering vitamin B. In this systematic review and meta-analysis, we address this topic and investigate whether oral supplementation of vitamin B can successfully prevent cognitive decline in cognitively unimpaired individuals. METHODS: A computerized systematic literature search was conducted using the electronic databases PubMed, Embase, and the Cochrane Library. Eligibility criteria included oral supplementation with vitamin B (B1, B6, folic acid, and B12) and the absence of cognitive impairment. A meta-analysis was conducted with "global cognition" as the primary outcome of this review. Secondary outcomes were changes in cognitive function in other cognitive domains reported in the included studies. Risk of bias was assessed according to the Cochrane Risk of Bias tool and the GRADE approach to establish the overall certainty of the evidence. RESULTS: The meta-analysis did not yield a significant overall effect of supplementation with vitamin B on cognitive function (Z = 0.87; p = 0.39; SMD, 0.02; 95% CI, - 0.034, 0.08). A sensitivity analysis focusing on specific risk factors did not alter this result. Some studies reported isolated significant effects of the intervention on secondary outcomes. However, these findings were outnumbered by the number of cognitive tests that did not yield significant effects. DISCUSSION: We found no overall evidence that oral vitamin B supplementation prevented cognitive decline. The isolated significant effects that were reported could be attributed to methodological issues. The results of this review do not provide evidence that population groups with certain risk factors would profit more from the intervention than others. Our findings do not apply to forms of administration other than oral supplementation nor do they offer information regarding the treatment of cognitively impaired individuals via the administration of vitamin B. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42017071692.
CRIS-Team Scopus Importer:2020-05-29
Keywords: Cognition[Mesh]; Dementia[Mesh]; Folic Acid[Mesh]; Prevention; Vitamin B12[Mesh]; Vitamin B6[Mesh]